TEACHING DESCRIPTIVE WRITING THROUGH GENRE-BASED APPROACH - Fadlin Hadini; Muhammad Yunus; Fiftinova Fiftinova (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2015)
Abstract: The objective of this study was to find out whether or not there was any significant improvement of students‟ skills in writing descriptive texts after they were taught by using Genre-Based Approach. The method of this study was a pre-experimental study which used one group pretest-posttest design. The population was the eighth grade students of SMP N 14, in the academic year 2013/2014 with the total number of 399 students. The total number of the sample was 39 students. The experimental group was taught writing descriptive texts by using Genre-Based Approach. To gain the data, the pretest and posttest were administered to the experimental group. The data obtained from the test were analyzed by using paired sample t-test. The calculation was done by using Statistical Package for Social Science 21 (SPSS 21). The results of test showed that the students got better scores in the posttest than in the pretest. The mean score of pretest was 44.79 while the mean score of posttest was 72.38. Therefore, there was a significant improvement of students‟ skills in writing descriptive texts after they were taught by using Genre-Based Approach. It was also found that the writing aspects namely, content, text organization, and language improved significantly. Conclusively, in this study, Genre-Based Approach can improve students‟ descriptive writing.Keywords: descriptive text, writing skill, genre-based approach, eight graders